Client’s Point of Views and Translators’ Decision Making - Risa Rumentha Simanjuntak (Bina Nusantara University, 2014)
This paper aims to make a critique to a chapter in Samuelsson-Brown’s (2010) A Practical Guide for Translators. The focus is on communication with clients for successful translation negotiations and decisions need to be fairly made. Following clients’ recommendations may result in intervening translators’ professionalism and impartiality. The paper argued that balance should be maintained between considering the needs of the clients and maintaining fidelity and impartiality, including ethics and morality aspects that often intertwined with the text.